Idea nowego początku w słowackich wizjach dziejów z połowy XIX wieku - Anna Kobylińska (Slavia Meridionalis, 2014)
The idea of new beginning in the Slovak vision of history from the mid-19th century The point of this paper is to show that the idea of new beginning was clearly present in mid-19th century Slovak literature. This idea became the means of conveying revisions of Slovak history. It was also a sign of a deep cultural change, resulting from factors including secularisation and the influence of nationalist ideology. The direction of change can be observed in selected works by Janko Kráľ, Viliam Pauliny-Tóth, and Jonáš Záborský. These writers challenge the optimistic view of the world by seeing in it a fundamental mistake that needs to be corrected. They propose correcting the myth of origin (Christian, national), but on the basis of a hermetic paradigm (magic and/or gnosis). Thus they create a false dimension of transcendence that becomes the foundation of the “new era”.